Digital Taxes and the Global Economy: A Multinational Literature Perspective - Purnamasari, Tika (Advances in Taxation Research, 2024)
Purpose: This research aims to explore the multifaceted landscape of digital taxation in the global economy and explain its implications for businesses, consumers, and governments worldwide. Research Design and Methodology: This research analyzes the challenges and opportunities associated with digital taxes using a comprehensive literature review approach. It adopts a qualitative analysis framework to collate findings from scholarly articles, policy documents, and reports. Findings and Discussion: This research highlights key themes and relevant perspectives in the digital tax discourse, including its impact on competitiveness, consumer behavior, and enforcement mechanisms. The findings demonstrate the importance of a deeper understanding of the complexities of digital taxes and potential avenues for future research. Implications: By integrating digital taxes into broader discussions on tax policy and economic governance, policymakers can foster a more inclusive, equitable, and sustainable tax environment in the digital age. The research also emphasizes the importance of cross-disciplinary collaboration and stakeholder engagement in effectively addressing digital tax challenges and opportunities.